NLRP3 Inflammasome in Metabolic-Associated Kidney Diseases: An Update - Xiong, Wei; Meng, Xian-Fang; Zhang, Chun (Frontiers in Immunology, 2021)
Metabolic syndrome (MS) is a group of complex metabolic disorders syndrome, which refers to the pathological state of metabolism disorder of protein, fat, carbohydrate and other substances in human body. The kidney is an important organ of metabolism, and various metabolic disorders can lead to the abnormalities in the structure and function of the kidney. The recognition of pathogenesis and treatment measures of renal damage in MS is a very important part for the renal function preserve. Inflammatory response caused by various metabolic factors is a protective mechanism of the body, but persistent inflammation will become a harmful factor and aggravate kidney damage. Inflammasomes are sensors of the innate immune system that play crucial roles in initiating inflammation in response to acute infections and chronic diseases. They are multiprotein complex composed of cytoplasmic sensors (mainly NLR family members), apoptosis-associated speck-like protein (ASC or PYCARD) and pro-caspase-1. After receiving exogenous and endogenous stimuli, the sensors begin to assemble inflammasome and then promote the release of inflammatory cytokines IL-1β and IL-18, resulting in a special way of cell death named pyroptosis. In the kidney, NLRP3 inflammasome can be activated by a variety of pathways, which eventually leads to inflammatory infiltration, renal intrinsic cell damage and renal function decline. This paper reviews the function and specific regulatory mechanism of inflammasome in kidney damage caused by various metabolic disorders, which will provide a new therapeutic perspective and targets for kidney diseases.